Mountain Bridge, 1891 - Pickford, Joel:::::::::
George Pickford, 30, Ida Studer Pickford, 25 and their son Rollin A. Pickford Sr., 4 (the artist's father) joined a group of friends for a mountain excursion and picnic. The second digital file shows a closeup detail of the Pickfords.